Compartimentação das Unidades de Paisagem do Litoral Oriental e Agreste do Rio Grande do Norte, Brasil - Souza, Ana Caroline Damasceno (2020)
The landscapes units are homogeneous or with similar characteristics and physiognomically can be identified from a spacial scale. The main goal of this work consisted in the realization of the compartimentation, delimitation and quantification of the landscapes on a Geofacie level (1:50.000) in the Eastern Coast and Wildside of Rio Grande do Norte, based on its physiognomy. For the analysis of the units, it was used the norms of the Geosystemic concept, which according to Georges Bertrand, the landscape is alwaysin a constant process of change. Encompassing the analysis, the result and the interactions between the ecological potential, biological exploration and antrophic actions, besides that, the application of the taxonomic system of the landscape. In the execution of the mappings, it was used Sentinel- A2 e B2 satellite images with spacial resolution of 10 meters, vectorized manually in environment of geographic information system, also it was used in the validation of themap in field projects a technical sheet to help the register of the information about the elements of the landscape, a Phantom 3 Advanced drone, GNSS device to locate points of doubts and photographical registration. Therefore, the mapped landscapes in 6.402,73 square kilometres of the Rio Grande do Norte territory, it was subdivided in a morphoclimatic domain (rainforest domain), a transition area (wildside) and a fragmentation of the Cerrado; four natural regions; and nine geocomplexes. Those, fragmented in 63 Geofacies, in which, 11 Geofacies were identified in the geocomplexes of humid coastal plains, 5 in the riverine humid plains, 8 in the humid coastal trays, 10 in the coastal plains of the state's wildside, 6 in the riverine plains of the state's wildside, 10 in the wildside trays, 4 in the depression of the state's wildside, 7 in the trays in the fragmentation of the Cerrado enclave, and 3 in the riverine plains in the of the Cerrado enclave. In general, the units of landscapes that prevail in the study area were the farming activities (permanent and temporary agricultural and pasture) occupying 3.439,26 square kilometres and 55% of the mapped territory, specially in the wildside of the state and in the humid coastal trays; and, the urban areas with 527,96 square kilometres and 8% of the area, focusing on the metropolitan area of Natal because of its intense urbanisation, with a population of more than 1,600,000 habitants. So, using the methodology applied in the construction of this research, it was possible to achieve the goals here proposed and fill some of the gaps existed in the landscape's science on the territory studied, shining a light for the future projects that can understand the dynamics of the landscapes.